The tortoise and the hare: How North's institutional ideas resolved a 19th century Australian fable - O'Connell, D.; Austen, Siobhan (2017)
Our paper adopts Douglass North's institutional framework to explain why the colonies of Western Australia and South Australia, established in 1829 and 1836, respectively, had considerable disparities in economic growth up the end of 1900. Both colonies were established under different modes of organisation (colonisation). The method adopted for WA harked back to Mercantilism, famously condemned by Adam Smith because it led to under-investment in, and over-exploitation of, colonial assets. SA on the other hand was the product of a radical new theory in colonisation proposed by Edward Gibbon Wakefield whereby land, instead of being given away as in WA, was sold at a fixed price with the proceeds being used to subsidise gender-balanced immigration. Outcomes suggest that SA's method of 'systematic colonisation' introduced a better institutional matrix, compared to the initial institutions seeded in WA, allowing SA's economy to develop sooner and at a higher rate of growth. However, once the detrimental effects of its method of foundation were eliminated, occurring on the eve of one of the largest gold discoveries of modern times, WA's institutions finally provided the necessary incentives for economic development such that by the end of 1900, it had equalled SA's level of economic output if not exceeded it.